Pandemic Impact on Islamic Financial Literacy: A Study in Bojonegoro Regency - Sri Anugrah Natalina; Arif Zunaidi (Prodi Ekonomi Syariah STAI Al-Azhar Menganti Gresik, 2023)
The purpose of this study is to determine the influence of decisions on becoming a customer. The research design this time is quantitative research. The data will be processed with a simple regression analysis. The analysis uses simple chart analysis to determine the amount of independence (Islamic financial literacy) due to instability (the decision to become a customer of an Islamic bank). The decision to become a customer is influenced by financial literacy, the financial literacy coefficient value of 0.336 states that if there is an increase in the unit's financial literacy, the decision to become a customer increases by 0.336 (33.6%), assuming other variables are considered constant. And also the Islamic financial literacy variable has a positive influence on decision-making to become a customer in Islamic banks. The result of the coefficient of determination (R²) is 0.15 or 15%, so it can be concluded that the influence of the Islamic financial literacy variable (X) in making decisions to become customers in Islamic banks (Y) has a percentage of 15%, while the remaining 85% influenced by other variables outside this study. The difference in this study is the selection of sample characteristics and research areas.